PERBANDINGAN KANDUNGAN FITOKIMIA PADA TEH PUTIH DAN TEH HIJAU DENGAN METODE HPLC - Rasyid Avicena; Sri Anna Marliyati; Budi Setiawan (UHAMKA PRESS, 2023)
Tea or Camellia sinensis is reported to contain as many as 4000 bioactive components, one of third are polyphenols. Polyphenols found in tea or Camellia sinensis are catechins, which consist of several types, one of which is Epigallocathecin-3-gallate (EGCG). Assessment of catechin and EGCG levels using HPLC due to considerations of efficiency, speed, and reduction of analysis costs which are also characteristic of HPLC. The aim of this study was to determine and compare the phytochemical content of catechin and EGCG compounds in white and green tea using the HPLC method. The research design used was a comparative analytical design. The main materials used were white tea and green tea from the Tea and Kina Research Center (PPTK), Gambung. The test conducted was a phytochemical examination of catechins and EGCG of white and green tea using the HPLC method in two replication. The results showed that the average catechin content in white tea was greater than that in green tea, which is 2.057±0,12% (w/b) in white tea, and 1.328±0,03% (w/b) in green tea. EGCG content in white tea has an average of 9.349±0,09% (w/b) and is greater than the average EGCG content in green tea which is only 8.037±0,05% (w/b). This is also reinforced by the statistical analysis results using an independent sample t-test of catechin and EGCG content in white and green tea which showed a significant difference. The conclusion is white tea has a greater catechin and EGCG content compared to green tea.